The Relevance of Crowdfunding: The Impact on the Innovation Process of Small Entrepreneurial Firms - Scholz, Nadine (Springer, 2015)
Nadine Scholz shows that crowdfunding potentially shortens the development cycle of new products, thus enabling an earlier market entry. Hence, crowdfunding serves as a multifaceted early-stage support instrument for innovation implementation facilitated by the crowd's resources. It not only provides upfront cash for product development and production, more importantly it enables a firm to show traction through the validation of the market demand that is based on the crowd's function as information multiplicator generating public exposure and feedback.